Política criminal: un mecanismo de poder punitivo y control social en Ecuador. - Vásquez Chicaiza, Franklin Patricio (2022)
This article aims to briefly describe the Criminal Policy in Ecuador as a mechanism of punitive power and social control, based on the theoretical foundations of important figures in Criminal Law. The main regulatory bodies that generate standards and guidelines of the Criminal Policy are identified, as well as the succinct identification of the standards and dimensions that would allow the adequate formulation of strategies for an effective implementation of the Criminal Policy in the country. Methodologically, the research was carried out using the critical analytical method, with a qualitative approach, applying the historical-legal methodological modes; socio-legal; and, normative-legal. Regarding data collection and selection techniques, the technique of documentary analysis and interview was used. Finally, the depth of the research is critical-descriptive. The described methodological application made it possible to identify important characteristics of punitive power, such as the decision-making of state power and its coercive nature for compliance with the established norm. Among one of its main findings are the legal, economic, social and cultural realities that require state intervention for an adequate materialization of criminal policy.